2021
DOI: 10.1101/2021.03.02.433228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the generalizability of diffusion MRI signal representations across acquisition parameters, sequences and tissue types: chronicles of the MEMENTO challenge

Abstract: Diffusion MRI (dMRI) has become an invaluable tool to assess the microstructural organization of brain tissue. Depending on the specific acquisition settings, the dMRI signal encodes specific properties of the underlying diffusion process. In the last two decades, several signal representations have been proposed to fit the dMRI signal and decode such properties. Most methods, however, are tested and developed on a limited amount of data, and their applicability to other acquisition schemes remains unknown. Wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
3
2
0
Order By: Relevance
“…Values may locally reach more than 40, and the majority lie in a suitable range. The SNR was on average 18 (GM) to 23 (WM), which is typical for a clinical study, and in line with commonly available research datasets (e.g., the SNR of the MASSIVE 38 ), is around 16 39 . While differences between DKI estimates with and without the MK‐Curve method are expected to decrease with increasing SNR, in their original work, Zhang et al showed that the MK‐Curve method also improved DKI estimates with high quality data, such as those from the Human Connectome Project 15 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Values may locally reach more than 40, and the majority lie in a suitable range. The SNR was on average 18 (GM) to 23 (WM), which is typical for a clinical study, and in line with commonly available research datasets (e.g., the SNR of the MASSIVE 38 ), is around 16 39 . While differences between DKI estimates with and without the MK‐Curve method are expected to decrease with increasing SNR, in their original work, Zhang et al showed that the MK‐Curve method also improved DKI estimates with high quality data, such as those from the Human Connectome Project 15 .…”
Section: Discussionsupporting
confidence: 75%
“…The SNR was on average 18 (GM) to 23 (WM), which is typical for a clinical study, and in line with commonly available research datasets (e.g., the SNR of the MASSIVE 38 ), is around 16. 39 While differences between DKI estimates with and without the MK-Curve method are expected to decrease with increasing SNR, in their original work, Zhang et al showed that the MK-Curve method also improved DKI estimates with high quality data, such as those from the Human Connectome Project. 15 Accordingly, we recommend the use of the MK-Curve method or other recently proposed alternatives, 10,12,14 when fitting DKI to both clinical and research quality data.…”
Section: Test-retest Assessmentsmentioning
confidence: 99%
“…Figure 12 shows the MAPE of MD for different sources of variation. Most noticeable, MD is highly different when calculated using two different b-values, as expected [3, 25, 32, 75, 76], followed by differences due to vendors. Differences across RESCAN, SCAN, RES, and DIR are typically <5%.…”
Section: Resultssupporting
confidence: 62%
“…12 shows the MAPE of MD for different sources of variation. Most noticeable, MD is highly different when calculated using two different b-values, as expected ( Novikov et al, 2018 ; Landman et al, 2007 ; Jones, 2004 ; De Luca et al, 2021 ; DK Jones et al, 1999), followed by differences due to vendors. Differences across RESCAN, SCAN, RES, and DIR are typically < 5%.…”
Section: Resultssupporting
confidence: 60%